DIGITALIZED ELECTRONIC PAY SLIP ISSUANCE APPLICATION AT NIAS POLICE - Wariyus Halawa; Maria Magdalena Bate’e; Ingin Berita Jaya Harefa; Eliagus Telaumbanua (Jurnal Ilmiah METADATA, 2026)
The development of information technology encourages government agencies to implement digitalization in administrative processes to improve efficiency, transparency, and accountability of services. One aspect of administration that is still largely managed manually is the management of employee pay slips, which has the potential to cause delays, miscalculations, and inefficient use of resources. This study aims to design and implement a digitalization-based electronic pay slip issuance application at the Nias Police. The system development method used is the Waterfall method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The developed application is web-based with two levels of users: financial administrators and employees. The results of the study indicate that the implementation of the electronic pay slip application can accelerate the pay slip issuance process, improve calculation accuracy, strengthen data security, and increase transparency and employee satisfaction. Thus, this application is considered effective as a digital solution for payroll administration and supports government policies related to the Electronic-Based Government System (SPBE).